Food waste in Czech households - Hrubá, Anna; Mokrejšová, Veronika, 1985-; Filipová, Alena, 1965-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The bachelor thesis addresses food waste in Czech households. Its main objective was to determine the proportion of food waste and the channels through which it exits, while also examining the impact of waste infrastructure on consumer behavior. Based on the collected data, the thesis proposes measures for a municipality to support optimal disposal and prevent the generation of food waste.
Vedoucí práce: Veronika Mokrejšová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses